ANALISIS LAJU PERTUMBUHAN KONTRIBUSI PKB, PBBKB DAN BBNKB TERHADAP PENDAPATAN ASLI DAERAH (STUDI KASUS TERHADAP PADA JAWA BARAT DAN DKI JAKARTA Periode Tahun 2015-2019) - Raynaldo Free Altrio; Bani Saad (Journal of Accounting, Management and Islamic Economics, 2023)
The purpose of this study is to find out the growth rate and tax contribution generated by Motor Vehicle Tax (PKB), Motor Vehicle Fuel Tax (UNKB) and Motor Vehicle Name Duty (BBNKB) in West Java province and DKI Jakarta with research range 2015-2019. This type of research is quantitative descriptive with the type of data used, namely primary and secondary data. The analysis used is the analysis of growth rates and contributions. The results of the study showed that the growth rate of PKB, UNKB and BBNKB in West Java and DKI Jakarta annually experienced ups and downs, with the highest growth rate averaging 12.39% in DKI Jakarta province with unsuccessful growth rate criteria. While the contribution of PKB in West Java Province averages 36.54% annually to Regional Original Income (PAD) with quite good criteria.